[OA194] Calculation of the patient size for abdominal radiography in terms of water equivalent diameter. (August 2018) - Dedulle, An; Fitousi, Niki; Jacobs, Jurgen; Bosmans, Hilde
Abstract : Purpose: Estimate the patient size, in terms of water equivalent diameter (WED), for conventional abdominal anterior-posterior (AP) radiography by using parameters available in the DICOM-header. Methods: The hypothesis of the present project was that the ratio of the incident air-kerma on the patient to the detector air-kerma relates to the patient size in conventional radiography. The incident air-kerma to the patient is provided by the dose area product (DAP) divided by the exposed area ( A exp ) . On the other hand, the standardized exposure index (EI)[1] is related to the detector air-kerma. Thus the ratio of both is expected to be associated to the patient size: EI DAP / A exp ∼ size patient . This hypothesis was tested on 120 adult patients who had an abdominal AP radiography and abdominal computed tomography (CT) scan within 1 year. The DAP, A exp and EI were extracted for every radiography from the dose management platform used in the hospital. The CT images were used to calculate the average WED CT over all axial slices[2] . The WED CT was plotted against the ratio ( EI DAP / A exp ) from the radiography and a curve fit was applied. The methodology was validated on 18 new patients with both an abdominal radiography and CT. The estimated WED ( WED est ) of these patients was found by using their DAP, A exp, EI and the previously fitted curve. The WED est was then compared to the WED as calculated from their CT ( WED CT ) . Results: An exponential curve fit was applied to the data with a good correlation of R 2 = 0.84 between the WED CT and the ratio EI DAP / A exp . In the validation part, the mean percentage difference between WED est and WED CT of the new patients was −1% and all differences were within ± 10%. Conclusions: The proposed and validated methodology allows for the calculation of an attenuation-based patient size metric for conventional radiography using parameters captured by a dose management platform from the DICOM-header.